Retrospective study showed that blood sampling errors risked children's well-being and safety in a Swedish paediatric tertiary care. - Hjelmgren, Henrik; Nilsson, Anna; Andersson-Papadogiannakis, Nina; Ritzmo, Carina; Ygge, Britt-Marie; Nordlund, Björn (Acta Paediatrica, 2018)
Aim: Blood analyses containing preanalytical errors (PAEs) are hazardous for patients. This study investigated the frequency of PAEs in blood analysis and the corresponding quality indicators of the sampling process in Swedish paediatric tertiary care.Methods: Data were retrieved from the laboratory at Astrid Lindgren Children's Hospital between 2013 and 2014. Preanalytical blood sampling performance was analysed according to the Six Sigma scale, ranging from 0 to 6 (933 137-3.4 defects per million [DPM]).Results: Of the 1 148 716 analyses, 61 656 (5.4%) were rejected due to PAEs. The PAEs ranged between hospital specialities from 1.9 to 9.4% (p < 0.001) and work shift times, from 6.0% in the day to 5.7% in the evening and 4.3% at night (p values <0.001). Clotting was the most prominent error (51.3%), affecting mostly haematology and coagulation analyses. Incorrectly filled samples represented almost 25% of all PAEs, with effects on chemistry, haematology and coagulation analyses. The sigma score for the overall preanalytical phase (3.2) corresponded to 44 565 DPM.Conclusion: Samples with PAEs were frequently clotted and insufficiently filled, and the distribution of errors varied within working shifts and specific analyses. The overall quality control in paediatric blood sampling was barely acceptable.